Proteins that bind the Src homology 3 domain of CrkI have distinct roles in Crk transformation - Zheng, Ji (2010)
The v-Crk oncogene product consists of two protein interaction modules, a Src homology 2 (SH2) domain and an SH3 domain. Overexpression of CrkI, the cellular homolog of v-Crk, transforms mouse fibroblasts, and elevated CrkI expression is observed in several human cancers. The SH2 and SH3 domains of Crk are required for transformation, but the identity of the critical cellular binding partners is not known. A number of candidate Crk SH3 binding proteins have been identified, including the nonreceptor tyrosine kinases c-Abl and Arg, and the guanine nucleotide exchange proteins C3G, SOS1 and DOCK180. The aim of this study is to determine which of these are required for transformation by CrkI. We found that shRNA-mediated knockdown of C3G or SOS1 suppressed anchorage-independent growth of NIH-3T3 cells overexpressing CrkI, while knockdown of SOS1 alone was sufficient to suppress tumor formation by these cells in nude mice. Knockdown of C3G was sufficient to revert morphological changes induced by CrkI expression. By contrast, knockdown of Abl family kinases or their inhibition with imatinib enhanced anchorage-independent growth and tumorigenesis induced by Crk. These results demonstrate that SOS1 is essential for CrkI-induced fibroblast transformation, and also reveal a surprising negative role for Abl kinases in Crk transformation.